Graphene addition to MgB2 superconductor obtained by ex-situ spark plasma sintering technique. (May 2016) - Aldica, G.; Burdusel, M.; Popa, S.; Hayasaka, Y.; Badica, P.
Graphical abstract: Highlights: Graphene-added dense MgB2 was prepared by ex-situ spark plasma sintering. There is a limited interaction between graphene and MgB2 . Addition of graphene (G) shows a small enhancement of J c and μ 0 H irr . G is one of the least effective C-containing additions. Abstract: Graphene nanopowder (G) with average thickness particle size of about 6–8 nm was added to MgB2 commercial powder. Starting composition was (MgB2 )(1− x ) (G) x, x = 0.0125, 0.025, 0.05. Processing was performed by Spark Plasma Sintering (SPS) technique. All added samples have high density (above 95%). The critical temperature ( T c ) and the lattice parameter a ( c -axis lattice parameter is constant) show a small variation suggesting that carbon substitution for boron is low. TEM observations show the presence of un-reacted graphene plates supporting the T c and structural results. It also indicates that G-addition does not modify the MgB2 microstructure. Despite this, there is an optimum doped sample (MgB2 )0.9875 (G)0.0125 for which the critical current density at temperatures below 25 K is slightly higher at high magnetic fields than for the pristine sample. The addition of G is found as one of the least effective C-source additions enhancing J c . We discuss results as being strongly related to variation of the residual stress.